New and rare lichens and lichenicolous fungi for the Left- Bank part of Ukraine from the Seversky Donets River basin (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Data on the 22 new and rare species of lichens and lichenicolous fungi for the Left-Bank part of Ukraine from Seversky Donets River basin are given. Among them, Bacidia fraxinea Lönnr., Caloplaca sterilis Šoun, Khodos. & Vondrák, Fuscidea arboricola Coppins & Tønsberg, Intralichen baccisporus D. Hawsksw. & M.S. Cole, Xanthocarpia marmorata (Bagl.) Frödén, Arup & Søchting and Xanthoriicola physciae (Kalchbr.) D. Hawksw. are reported for the first time for the Left-Bank part of Ukraine. The other species, such as Caloplaca grimmiae (Nyl.) H. Olivier, Chaenotheca brunneola (Ach.) Müll. Arg., Ch. furfuracea (L.) Tibell, Coenogonium pineti (Ach.) Lücking & Lumbsch, Cyphelium notarisii (Tul.) Blomb. & Forssell, Dimelaena oreina (Ach.) Norman, Lichenothelia convexa Henssen, Protoparmeliopsis laatokkensis (Räsänen) Moberg & R. Sant, Placynthiella icmalea (Ach.) Coppins & P. James, Pyrenodesmia concreticola (Vondrák & Khodos.) Søchting, Arup & Frödén, Ramalina capitata (Ach.) Nyl., Rinodina guzzinii Jatta, Sarcogyne privigna (Ach.) A. Massal., Trapelia glebulosa (Sm.) J.R. Laundon, T. obtegens (Th. Fr.) Hertel and Xanthocarpia crenulatella (Nyl.) Frödén, Arup & Søchting are rare.
Keywords: new and rare species, lichens, lichenicolous fungi, Left-Bank Ukraine.